Severe linezolid-induced lactic acidosis in a child with acute lymphoblastic leukemia: A case report - Smolka, Vratislav; Rohanova, Marie; Ludikova, Barbora; Novak, Zbynek; Zapalka, Martin; Pospisilova, Dagmar; Volejnikova, Jana (Journal of infection and chemotherapy, 2020)
Linezolid is an antibiotic increasingly used for treatment of resistant Gram-positive infections, which blocks bacterial proteosythesis through direct inhibition of mitochondrial ribosomes. The most common adverse effects of linezolid include gastrointestinal symtoms, peripheral neuropathy, bone marrow depression and lactic acidosis. Here we present a rare case of a 9-year-old female, a survivor of acute lymphoblastic leukemia (ALL) and a hematopoietic stem cell transplant (HSCT), who developed life-threatening lactic acidosis with vomiting, impaired consciousness and Kussmaul breathing after 51 days of intravenous linezolid administration due to mycobacterial infection. She fully recovered after drug discontinuation and normalization of the plasma levels. We conclude that plasma lactate concentrations should be monitored closely during any linezolid treatment, particularly in patients with hepatic or renal dysfunction.
Keywords: linezolid; acidóza laktátová; akutní lymfatická leukemie; antibakteriální látky; Plasma concentration; lidé; Child; dítě; Adverse event; Anti-Bacterial Agents; ženské pohlaví; Humans; Bacteria; Acidosis, Lactic; Female; Linezolid; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Lactic acidosis